The doxa of Christ and his followers in the fourth Gospel : an inquiry into the meaning and background of doxa in John 17:22 - Van der Watt, J.G. (Jan Gabriel), 1952- (University of Pretoria, 2013)
Thesis (PhD (New Testament Studies))--University of Pretoria, 2008.